Recreação e ensinamento matemático através de jogos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The purpose of this study was to understand the functionality of the mathematical games worked in the 6th year, analyzing the construction of knowledge, where playfulness is part, in a pleasurable way in the teaching and learning process. The research method was based on the bibliographical studies to better understand the theme and through the field research, as well as the observations made in locus, being carried out application of a questionnaire in order to make a parallel between the theory and the actions of the teachers of mathematics in the educational context. It was verified that mathematical games and playful aspects are undoubtedly important in the construction of students' knowledge in the initial phase of elementary school, taking into account the development of skills and abilities of contents, the reality of students, school and of the teaching and learning process. It is one of the ways in which the teaching of mathematics can get out of the routine and textbooks, starting with practice and interaction with concrete materials.
Keywords: Jogos; Lúdico; Ensino; Aprendizagem; habilidades; CNPQ:: CIÊNCIAS EXATAS E DA TERRA